1999
DOI: 10.1021/ja982898m
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Linear Thiophenolate-Bridged Heterotrinuclear Complexes [LFeMFeL]n+ (M = Cr, Co, Fe; n = 1−3):  Localized vs Delocalized Models

Abstract: The reaction of mononuclear [LFeIII] where L represents the trianionic ligand 1,4,7-tris(4-tert-butyl-2-mercaptobenzyl)-1,4,7-triazacyclononane with CrSO4·5H2O, CoCl2·6H2O, or Fe(BF4)2·6H2O and subsequent oxidation with ferrocenium hexafluorophosphate or NO(BF4) or reduction with [(tmcn)Mo(CO)3] (tmcn = 1,4,7-trimethyl-1,4,7-triazacyclononane) produced an isostructural series of [LFeMFeL] n + complexes, the following salts of which were isolated as crystalline solids:  (i) [LFeCrFeL](PF6) n with n = 1 (1a), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 100 publications
(128 reference statements)
7
71
0
Order By: Relevance
“…This allowed us to conclude that the Cu III compound is likely a www.eurjic.org Table 1. Distances and angles (Å and°), at given copper oxidation number (ON), obtained by geometry optimisation, at B3LYP/6-31G(d,p) level for different spin multiplicity (Spin), by X-ray crystallography [2] and by EXAFS analysis and calculated difference energy values ∆E (eV) [2] Both theoretical and experimental data confirm that a change in the copper oxidation number from ii to iii de-creases the metalϪligand distances of the atoms of the first coordination shell; [1,2,7,8] conversely, an increase in the spin multiplicity, at a given oxidation state of the metal, increases the same metalϪligand distances (see, for example, the calculated CuϪS or CuϪN distances).…”
Section: Exafs Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…This allowed us to conclude that the Cu III compound is likely a www.eurjic.org Table 1. Distances and angles (Å and°), at given copper oxidation number (ON), obtained by geometry optimisation, at B3LYP/6-31G(d,p) level for different spin multiplicity (Spin), by X-ray crystallography [2] and by EXAFS analysis and calculated difference energy values ∆E (eV) [2] Both theoretical and experimental data confirm that a change in the copper oxidation number from ii to iii de-creases the metalϪligand distances of the atoms of the first coordination shell; [1,2,7,8] conversely, an increase in the spin multiplicity, at a given oxidation state of the metal, increases the same metalϪligand distances (see, for example, the calculated CuϪS or CuϪN distances).…”
Section: Exafs Spectramentioning
confidence: 99%
“…Moreover, the shape and position of the absorption edge help to distinguish different oxidation states of the metal atoms in analogous complexes. [7] In particular, in the rising edge of the XAS spectra of the copper complex, a few weak peaks and shoulders might originate from transitions from 1s to 3d or 4p orbitals, which are typically attributed to bound state forbidden transitions. [6] This information is usually employed to determine the local symmetry of the transition-metal environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] In contrast, no examples of heterometallic vanadium/cobalt or vanadium/nickel thiolato complexes were found in the literature. A series of trinuclear metal complexes of the type [LMMЈML] n+ with L = 1,4,7-tris(4-tertbutyl-2-mercaptobenzyl)-1,4,7-triazacyclononane like [LCoNiCoL] n+ (n = 2-4), [LNiCoNiL] n+ (n = 1-3), [9] [LFeNiFeL] n+ (n = 2-4), [10] [LFeMFeL] n+ (M = Cr, Co; n = 1-3) [11] and [LFeMFeL] n+ (M = Ge, Sn; n = 2,3) [12] have been synthesised and characterised with respect to their magnetic exchange properties. It was shown that in these compounds the mechanism of spin coupling cannot be described exclusively in terms of the classical superexchange mechanisms but rather spin-dependent delocalisation by means of double exchange mechanisms [9] had to be invoked.…”
Section: Introductionmentioning
confidence: 99%
“…In a forthcoming publication [Glaser et al (1998)] we focus on the preparation of these complexes, whereas in this contribution we discuss the structural changes upon oxidation of the complexes determined by X-ray absorption spectroscopy. …”
mentioning
confidence: 99%